2010
DOI: 10.3109/08860221003728739
|View full text |Cite
|
Sign up to set email alerts
|

The dose of continuous renal replacement therapy for acute renal failure: a systematic review and meta-analysis

Abstract: Objectives: To conduct a systematic review of the literature to summarize the best available evidence regarding the mortality and morbidity associated with differing dosing regimens of continuous renal replacement therapy (CRRT) for patients with acute renal failure (ARF) in an intensive care unit setting. Patients and Methods: We searched for randomized controlled trials in electronic databases from January 1990 through November 2009. Eligible trials compared two or more dosing regimens of CRRT in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…[20][21][22] Although, our findings are similar to prior studies, a strength of our analysis is the meta-regression analysis with evaluated the impact of patients with sepsis or septic shock on the overall pooled analysis. The meta-regression analysis indicated that heterogeneity due to a mixed population of sepsis and septic shock patients did not influence the pooled results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[20][21][22] Although, our findings are similar to prior studies, a strength of our analysis is the meta-regression analysis with evaluated the impact of patients with sepsis or septic shock on the overall pooled analysis. The meta-regression analysis indicated that heterogeneity due to a mixed population of sepsis and septic shock patients did not influence the pooled results.…”
Section: Discussionsupporting
confidence: 80%
“…These studies found that high-dose CRRT was not associated with a decrease in mortality in patients with AKI. [20][21][22] Since the publication of these reviews, additional clinical studies have been published that addressed the use of CRRT in AKI. 23 24 Prior reviews have addressed both haemofiltration and haemodialysis, which may not provide sufficient data with respect to either method.…”
Section: Introductionmentioning
confidence: 99%
“…An association has been shown between dose of renal replacement therapy (RRT) delivered and survival in an intensive care setting. 1,2 While this is controversial, 3,4 patients in two recent large trials 5,6 where specific efforts were made to optimise dose delivery showed better overall survival rates than seen in recent historical controls. 7 While there is still uncertainty surrounding the relationship between dose and survival, there is widespread agreement that clearance is the best way to quantify continuous renal replacement dose.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study with significant methodological limitations reported a reduction in the use of vasopressors in the experimental group (36), and none of the trials reviewed reported an improvement in gas exchange, duration of mechanical ventilation, development of MODS or length of stay. Respect to other outcomes, two recent meta-analyses (77,78) found no effect of high-dose renal replacement therapy on dialysis dependence or length of stay in patients with ARF.…”
Section: Efficacy Of Crrt In Patients With Severe Sepsis or Septic Shockmentioning
confidence: 99%